Analysis of calculation methods for life cycle greenhouse gas emissions for road sector - Vorobjovas, Viktoras; Motiejūnas, Algirdas; Ratkevičius, Tomas; Zagorskis, Alvydas; Danila, Vaidotas (International Conference “Environmental Engineering”, 2017)
Climate change is one of the main nowadays problem in the world. The politics and strategies for climate change and tools for reduction of greenhouse gas (GHG) emissions and green technologies are created and implemented. Mainly it is focused on energy, transport and construction sectors, which are related and plays a significant role in the roads life cycle. Most of the carbon footprint emissions are generated by transport. The remaining emissions are generated during the road life cycle. Therefore, European and other countries use methods to calculate GHG emissions and evaluate the impact of road construction methods and technologies on the environment. Software tools for calculation GHG emissions are complicated, and it is not entirely clear what GHG emission amounts generate during different stages of road life cycle. Thus, the precision of the obtained results are often dependent on the sources and quantities of data, assumptions, and hypothesis. The use of more accurate and efficient calculation valuation methods could let to determine in which stages of road life cycle the largest carbon footprint emissions are generated, what advanced road construction methods and technologies could be used. Also, the road service life could be extended, the consumption of raw materials, repair, and maintenance costs could be reduced. Therefore the time-savings could be improved, and the impact on the environment could be reduced using these GHG calculation-evaluation methods.